Optimalisasi Pemberdayaan Keuangan Sosial Melalui Crowdfunding Online untuk Pengembangan Infrastruktur Wisata Desa - Wardayani; Supriyanto (Forum Kerjasama Pendidikan Tinggi, 2025)
This community service aims to empower village entrepreneurs and managers of Village-Owned Enterprises (BUMDes) to better understand financial management through training on the use of online crowdfunding in the development of village tourism infrastructure. This activity was carried out using a participatory approach through face-to-face training, case studies, and hands-on practice in campaign fundraising. Based on a survey of 20 participants before and after the training, there was a significant increase in understanding of the concept of crowdfunding, with the majority moving from a low level to moderate and high levels after the training. These findings align with recent research highlighting the importance of digital financial literacy and technology utilisation in village development (Rahmawati et al., 2024; Suvero et al., 2023; Zellatifanny & Mudjiyanto, 2024). Although the training successfully enhanced participants' capacity, the activity had limitations in terms of the number of respondents, the short duration of the training, and the absence of a directly implemented crowdfunding campaign. Therefore, the programme recommends ongoing mentoring and multi-stakeholder collaboration to ensure the sustainable use of crowdfunding as a village social finance tool and its direct impact on local tourism development